Voiding Disorders in Pediatrician's Practice. (November 2020) - Rakowska-Silska, Magda; Jobs, Katarzyna; Paturej, Aleksandra; Kalicki, Bolesław
Voiding disorders result usually from functional disturbance. However, relevant organic diseases must be excluded prior to diagnosis of functional disorders. Additional tests, such as urinalysis or abdominal ultrasound are required. Further diagnostics is necessary in the presence of alarm symptoms, such as secondary nocturnal enuresis, weak or intermittent urine flow, systemic symptoms, glucosuria, proteinuria, leukocyturia, erythrocyturia, skin lesions in the lumbar region, altered sensations in the perineum. Functional micturition disorders were thoroughly described in 2006, and revised in 2015 by ICCS (International Children's Continence Society) and are divided into storage symptoms (increased and decreased voiding frequency, incontinence, urgency, nocturia), voiding symptoms hesitancy, straining, weak stream, intermittency, dysuria), and symptoms that cannot be assigned to any of the above groups (voiding postponement, holding maneuvers, feeling of incomplete emptying, urinary retention, post micturition dribble, spraying of the urinary stream). Functional voiding disorders are frequently associated with constipation. Bladder and bowel dysfunction (BBD) is diagnosed when lower urinary tract symptoms are accompanied by problems with defecation. Monosymptomatic enuresis is the most common voiding disorder encountered by pediatricians. It is diagnosed in children older than 5 years without any other lower urinary tract symptoms. Other types of voiding disorders such as: non-monosymptomatic enuresis, overactive and underactive bladder, voiding postponement, bladder outlet obstruction, stress or giggle incontinence, urethrovaginal reflux usually require specialized diagnostics and therapy. Treatment of all types of functional voiding disorders is based on non-pharmacological recommendations (urotherapy), and such education should be implemented by primary care pediatricians.